The visual narrative of a Bubi and Galician arteducator travels to the classrooms of her two origins - López-Ganet, Tiffany (Rastros Rostros, 2023)
Introduction: This article pretends to share the autobiography’s possibilities to explore the migrant reality, gender, race or the sense of belonging through the arts and how this research reaches the schools. Methodology: From the author’s life story —a black, Bubi (original people of the Bioko island, Equatorial Guinea) and Galician (Galicia, Spain) woman who inhabits a mostly white environment— an Art-based Research methodology is created involving visual memories extracted from the domestic photographic archive and microtales connected to racist experiences. Results: Connecting the privacy of that self-perception with an afro, common and collective discourse, the experiences are extrapolated completing them with artistic and bibliographical references. Then art educational strategies are created to show the students a decolonial, anti-racist and afrofeminist discourse to work with them about respect, self-knowledge and non-discrimination. Conclusions: The author’s journey as the daughter of a migrant woman tells her diasporic reality through the photograph, video, collage and identity narratives and it reaches class-rooms from different educational centres of Spain, Canada, India and Equatorial Guinea. Of them all, this article focuses on its implementation in her two origins: Oleiros (A Coruña, Galicia, Spain) and Ela Nguema (Malabo, Equatorial Guinea).